Differences in Birth Size Associated with Preconception Maternal Nutrition Intervention Persist in Postnatal Growth Through 6 Months (OR10-05-19). (13th June 2019) - Krebs, Nancy; Hambidge, Michael; Westcott, Jamie; Garces, Ana; Lokangaka, Adrien; Dhaded, Sangappa; Ali, Sumera; Thorsten, Vanessa; Sridhar, Amaanti; Chowdhury, Dhuly; Das, Abhik; Group, Women First Study
Abstract: Objectives: Newborn size, including length, has been associated with later growth. Preconception nutrition supplementation in Women First (WF) trial ( clinicaltrials.gov NCT01883193) was associated with higher newborn length and lower rates of stunting. The objective was to examine postnatal growth outcomes through 6 mo in the WF offspring. Methods: Subjects were 2450 infants from the WF sites in Democratic Republic of Congo (DRC), Guatemala, India, and Pakistan with the 3 WF arms maintained: Arm 1 started a lipid-based nutrition supplement ≥ 3 mo prior to conception; Arm 2 started same supplement at ∼11 wk gestation; and Arm 3 received no trial supplements. Maternal supplementation was discontinued at delivery. Anthropometric measurements were obtained at birth, 0.5, 1, 3, and 6 mo; Z-scores were calculated from WHO Child Growth Standards. Primary and secondary outcomes were analyzed using longitudinal generalized estimating equations accounting for the correlation of repeated measures over time and study cluster. Intervention effects were evaluated within each site as well as overall, adjusting for site and baseline maternal covariates that differed by arm. Statistical interaction between arm and infant sex was evaluated and included if significant. Results: Longitudinal growth (length and weight) curves from 0–6 mo demonstrated differences by intervention arm, with Arms 1 and 2 more favorable compared to Arm 3 (Table + LAZ in Figure). Relative risks (RR) for stunting were significantly lower for Arms 1 and 2 (vs. Arm 3) (Table). Site-specific analyses revealed some site differences warranting further exploration. Conclusions: Without any postnatal intervention, differences in fetal growth evident at birth persisted at 6 months. Funding Sources: Bill & Melinda Gates Foundation; NIH, NICHD & ODS. Supporting Tables, Images and/or Graphs: